2009
DOI: 10.1074/jbc.m109.001800
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional Structure and Enzymatic Function of Proapoptotic Human p53-inducible Quinone Oxidoreductase PIG3

Abstract: Tumor suppressor p53 regulates the expression of p53-induced genes (PIG) that trigger apoptosis. PIG3 or TP53I3 is the only known member of the medium chain dehydrogenase/reductase superfamily induced by p53 and is used as a proapoptotic marker. Although the participation of PIG3 in the apoptotic pathway is proven, the protein and its mechanism of action were never characterized. We analyzed human PIG3 enzymatic function and found NADPH-dependent reductase activity with ortho-quinones, which is consistent with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
57
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 59 publications
2
57
0
Order By: Relevance
“…Recent research reported that overexpression of PIG3 accumulates ROS in vivo and in vitro; while an inactive PIG3 mutant (Ser151Val) does not [3]. Our result, H 2 O 2 stimulating PIG3 expression, implied that ROS may also contribute to PIG3 induction by ionizing radiation via the oxidative DNA damage mechanism.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Recent research reported that overexpression of PIG3 accumulates ROS in vivo and in vitro; while an inactive PIG3 mutant (Ser151Val) does not [3]. Our result, H 2 O 2 stimulating PIG3 expression, implied that ROS may also contribute to PIG3 induction by ionizing radiation via the oxidative DNA damage mechanism.…”
Section: Discussionsupporting
confidence: 54%
“…As consistent with its classification in the quinine oxidoreductase (QOR) family, PIG3 was confirmed an activity of NADPH dependent reductase with orthoquinones [3]. In addition, in vitro activation and in vivo overexpression of PIG3 was demonstrated to accumulate reactive oxygen species (ROS), while an inactive PIG3 mutant (Ser151Val) did not produce ROS in cells, indicating that enzymatic active protein is necessary for its function [3]. PIG3 was also recently demonstrated to contribute to early cellular response to DNA damage induced by UV radiation and the DNA damaging-chemical neocarzinostatin through recruiting 53BP1, Mre11, Rad50 and Nbs1 to the sites of DNA break lesions and modulating intra-S and G2/M phase checkpoint [4].…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…Polyak et al [7] showed that redox active transcripts (PIGs) were markedly increased in p53-expressing cells. Recently, the enzymatic function of PIG3 was characterized as a prooxidant oxido-reductase and PIG3-induced ROS generation was detected in human colon cancer cells infected with virus carrying the PIG3 gene [20]. Sablina et al [21] also showed an increased ROS generation in lung carcinoma cells overexpressing the PIG3 gene, but they showed an even higher ROS production after infection with the PUMA gene.…”
Section: Discussionmentioning
confidence: 99%
“…Activated p53 increases cellular ROS levels by enhancing the transcription of proapoptotic genes, such as PIGs and Bax (Polyak et al, 1997;Kirkland et al, 2002). PIG3 shows sequence similarity with NQO, and influences the production of intracellular ROS (Porte et al, 2009). Thus, although PIG3 expression alone is insufficient to induce apoptosis (Polyak et al, 1997), PIG3 may be one of the factors involved in p53-induced apoptosis through ROS generation.…”
Section: Pig3 Is Involved In the Cell-cycle Checkpoint Pathwaymentioning
confidence: 99%